Game Edukasi Menggunakan Powerpoint dan Canva Sebagai Penunjang Pembelajaran di SMP Kristen 1 YPK Malang - Yurida Ekawati; Teguh Oktiarso; Sunday Noya; Meme Susilowati (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
This community service program was conducted at SMP Kristen 1 YPK Malang to enhance teachers’ and students’ skills in utilizing educational technology through game-based learning using Microsoft PowerPoint (PPT) and Canva. The initiative was motivated by the need to improve educators’ competencies in employing interactive applications to address student boredom and the monotonous learning process. The implementation method involved workshops combining interactive lectures, live demonstrations, independent practice, and project presentations. Participants created interactive quizzes, puzzles, and digital board games. The results indicated an improvement in participants’ skills in using hyperlinks, visual design, and creativity in developing game-based learning media. Technical challenges, such as limited internet access, were resolved through practical solutions. Overall, the program had a positive impact on participants’ motivation, engagement, and ability to integrate technology into learning activities. In the long term, these skills are expected to support teachers in designing more varied, interactive, and effective classroom learning.